Entrepreneurship and its Economical Value in a very Dynamic Business Environment - Ana-Maria Grigore; Irina-Maria Drăgan (Amfiteatru Economic)
The aim of this article is to enrich the vision regarding the connection between entrepreneurship and economic growth, focusing upon an economy in transition to a market economy. The authors of the present paper have developed an empirical model – based on a constant preoccupation to observe the impact of the entrepreneurial phenomenon on the free, emerging market in Romania – model which uses a number of variables which are believed to influence the critical mass of viable business existing in a dynamic environment. The proposed model identifies the factors that need to be activated in the current context to transfer the theoretical importance of SME’s in the truly complex world of an economy that desires to be prosperous. Then, the model was exposed to the test of the objective statistical and mathematical testing, starting from the results obtained from a survey of 536 entrepreneurs. The methodological approach makes use both of regression models, which use the relevant aspects from the survey, turned into quantitative or qualitative variables, and of the analysis of variance, with the aim of explaining the way in which the considered variables have managed to determine the economic growth, as well as of determining their importance and their influence. Finally, several conclusions have been outlined, regarding the economic policy measures that are needed and feasible in order to make the business environment in Romania more predictable and more friendly and, thus, to encourage entrepreneurship.